Cooling Tower Performance Analysis Using Range and Approach Method Unit 4 in Pt. Pertamina Geothermal Energy Kamojang Area - Ramadan, Ripa Hikmah; Sucita, Tasma (Journal La Multiapp, 2025)
Geothermal Power Plant (PLTP) is one of the renewable energy sources that supports the national energy transition. One of the important components in the PLTP system is the cooling tower which functions to lower the temperature of the condensed water so that it can be reused in the thermodynamic cycle. This study aims to analyze the performance of the cooling tower at PLTP Kamojang Unit 4 owned by Januari Pertamina Geothermal Januari using the Range and Approach methods based on the ASME PTC 23-2003 standard. Data were obtained from operational logsheets during the period from 4 to 10 January 2025 and analyzed using Microsoft Excel. The parameters observed included inlet water temperature, outlet water temperature, and wet bulb air temperature. The results of the analysis showed that the range value ranged from 35.61°C to 36.48°C, the approach value between 4.73°C to 5.12°C, and the effectiveness of the cooling tower was in the range of 87.42% to 88.52%. These values indicate that the cooling tower is still operating at high efficiency. Daily fluctuations in these values are influenced by environmental factors such as air humidity, wet bulb temperature, and variations in cooling load. In addition, internal factors such as fan conditions, water spraying, cooling water quality, and media packing conditions also contribute to system performance. Based on these results, it is recommended that regular monitoring and preventive maintenance be carried out to maintain the efficiency of the cooling system. With improvements and digitalization of monitoring, the cooling tower at PLTP Kamojang Unit 4 can continue to support power plant operations optimally and sustainably.